How Does Exploration of New Adventure Tourism Destinations in Bali? - Pande Putu Raditya; Dola Destiya Ripana; Upayana Wiguna Eka Saputra; Yovita Helena Junjanto (Politeknik Pariwisata Makassar, 2024)
Bali is one of the most prestigious tourism destinations in Indonesia that has begun to over tourism. On the other hand, nature landscape in Bali provides for adventure tourism which is underexplored. The novelty from this study is reveal how adventure tourism in Bali held, and factors that influence on adventure tourism. Data collected from focus group discussion with organization who have interest in mountain forest, rock climbing, and rafting in Bali. The research result describes how adventure tourism held consist bay three stages: pre exploration, exploration, and post-exploration. And what are the supported and unsupported factors to successfully that adventure tourism in Bali categorized in three main factors: external factor, internal factor, relationship factor. This research has implications for tourism public policy in Bali and tourist attraction managers.